An Idiosyncratic Approach in the Indonesia-Japan Collaboration to Advance Renewable Energy and Public Transportation in Semarang - Hartati, Anna Yulia; Yuwanto, Yuwanto; Yuwono, Teguh; Adnan, Muhammad (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2024)
This study explores the impact of a leader's characteristics, particularly idiosyncratic personality traits. A prominent case study involves Mayor Hendrar Prihadi of Semarang, Indonesia, whose unique and powerful influence has significantly shaped the success of cooperation between Indonesia and Japan in the city. This study uses qualitative descriptive research. This paper relies on primary data sources, in the form of interviews with key informants and secondary data, in the form of documentation studies from relevant sources. The study reveals that city diplomacy, as observed in Semarang, is strongly associated with the Mayor's personality, level of sensitivity in responding to global issues, the influence of Javanese cultural and religious values, personal and organizational principles, and motives aimed at providing benefits to the city, particularly in the effort to create a zero-carbon urban environment. These findings underscore the link between a leader's characteristics and the decision-making process in the realm of city diplomacy, emphasizing the multifaceted nature of personality elements that guide policy choices.